Learning networks: internalizing inspiring way of change in higher education - Díaz Noguera, María Dolores (2014)
The experience here presented between universities in two countries, on two continents, Argentina and Spain would be an example of what we are saying. This task is not easy since there are many oddities and those balances that must be addressed when geographic, thematic and strategic dimensions of different signs so they should estarse attentive to the paradoxes of varying degrees that go as producing cross, by example, we are witnessing a globalization of our students without need for physical mobility situation that occurs from the moment we use the tools of Web 2.0 related to shared projects between Higher Education. Objectives: In this paper we present the experiences of two universities developed during the 2012/2013 course, one located in the European context and the other in the Latin American context in the design, development and evaluation of a joint inter-university experience. The objectives were aimed at assessing the behavior of students in the collaborative learning activities and to assess network design an educational project that allows interaction across multipleformats and information exchange from using flexible methodologies to adapt to different situations. Participants: Participants were 150 students enrolled at University of Seville degrees in Education and the University of Mar del Plata, Argentina (72) where pursuing degrees in Accounting and Bachelor of Business Administration. Process: The start of the project was publicly announced in Spain and in Argentina in September. In the first contact activities were presented by teachers and students in a closed facebook "COMPETEP" group, allowing acquainted with the digital work environment and to respond to the difficulties that were emerging. In this respect, teachers design FAQ guide with questions, set the basic requirements to be met by projects and provided guidance on facebook for discussion of students and teachers that participants did not comment during the four -week phase debate to not interfere with the cognitive and communicative processes that were generated in unique environments given its geographical location and different disciplines of reference for each group of students. Subsequently, working groups (peer or peer) internally assigning roles to each team (coordinator, secretary, analyst, documentarian and evaluator) were configured: The challenge was aimed at starting the search and contextualization of a real organization of private, public or non-governmental. The next challenge was to conduct a needs assessment to identify what should be a problem and find a solution for formative and innovative considering market opportunities sociopolitical context and situation. The third challenge was to share information gathered by organizing debates and work for an oral presentation shared by virtually hangout. The fourth challenge, in the process, is to present a report on the work developing the institutions of the feasibility study and view later pooling the results obtained in the two countries. Results: Regarding the first objective, to evaluate the behavior of students in activities that build instances of collaborative learning, the data collected in COMPETEP associated with about 200 publications on the net where photographs, videos, articles, and books have been the subject of a factorial analysis made emerge the following dimensions: motivation (a), satisfaction (B), communication (C), collaboration (D) restraint (E), negotiation (F), discussion (G), and opinions (H).